2019
DOI: 10.3390/cryst9080406
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Metal-Organic Frameworks for Natural Gas Storage

Abstract: Methane can be stored by metal-organic frameworks (MOFs). However, there remain challenges in the implementation of MOFs for adsorbed natural gas (ANG) systems. These challenges include thermal management, storage capacity losses due to MOF packing and densification, and natural gas impurities. In this review, we discuss discoveries about how MOFs can be designed to address these three challenges. For example, Fe(bdp) (bdp 2− = 1,4-benzenedipyrazolate) was discovered to have intrinsic thermal management and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 104 publications
(131 reference statements)
0
32
0
Order By: Relevance
“…Furthermore, solvent exchange steps should be minimized to simplify the process. Adsorbent designs should consider such problems, in addition to packing losses and material cyclability [174]. For the practical implementation of such systems, thermal management, and the effect of impurities on the performance should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, solvent exchange steps should be minimized to simplify the process. Adsorbent designs should consider such problems, in addition to packing losses and material cyclability [174]. For the practical implementation of such systems, thermal management, and the effect of impurities on the performance should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…[ 22,65,83,161 ] Regeneration is another option to mitigate the adverse impact of impurity accumulation and regain the uptake performance of the ANG system. [ 162 ] In the case of Maxsorb MSC‐30 (a commercial AC adsorbent), a 50% deterioration in volumetric storage capacity was observed after 100 sorption cycles. [ 162 ] This deterioration could be mitigated by desorbing at 673 K under vacuum for 2 h. [ 162 ] Considering their thermal stability, a lower regeneration temperature may be required for MOF adsorbents.…”
Section: Technical Challenges Of Ang Systems For Onboard Applicationsmentioning
confidence: 99%
“…[ 162 ] In the case of Maxsorb MSC‐30 (a commercial AC adsorbent), a 50% deterioration in volumetric storage capacity was observed after 100 sorption cycles. [ 162 ] This deterioration could be mitigated by desorbing at 673 K under vacuum for 2 h. [ 162 ] Considering their thermal stability, a lower regeneration temperature may be required for MOF adsorbents. In terms of onboard applications, a strategic design could be proposed, in which the exchangeable NG storage tanks undergo a centralized regeneration at refueling stations.…”
Section: Technical Challenges Of Ang Systems For Onboard Applicationsmentioning
confidence: 99%
“…The textural characteristics of the activated carbons have been evaluated by N 2 adsorption at -196 ºC and CO 2 at 0 ºC [11,23] in a volumetric Autosorb-6B apparatus from Quantachrome. Before the analysis, the samples were outgassed at 250 ºC for 4 h.…”
Section: Textural Propertiesmentioning
confidence: 99%
“…To solve this problem, new materials have been tested with the aim to obtain high adsorption capacities in materials with high mechanical resistance [5,6,8]. Recent studies reported the preparation of HKUST-1 MOF in form of monolith that reported absolute volumetric methane and excess volumetric adsorption values of 259 and 230 V/V at 68 bar, respectively [11,12]. This monolith shows a delivery capacity, using the real bulk density, of 172 cm 3 (STP)cm −3 at 68 bar which are among the highest reported for monolithic materials, although the preparation of these monoliths are only tested in small monoliths [13].…”
Section: Introductionmentioning
confidence: 99%